Analisis Risiko Proses Pembuatan Kertas Kerja HPS dengan Metode FMEA - Dudi Hendra Fachrudin; Arinie Rizqyawan Rahayu (Jurnal Serambi Engineering, 2023)
PT XYZ is a company that is trusted to print banknotes, coins, non-cash coins and various other securities. In printing and producing, of course, each division requires tools and materials, therefore the role of the Procurement and Public Facilities Division is needed. In the Procurement Preparation Department, of course, there were problems in the process of making HPS working papers. The purpose of this study itself is to analyze the risks in the process of making HPS working papers using the FMEA method. This methodbegins with identifying activities, then analyzing risk events and the causes of these risk events, and finally how easily these risk events can be detected. The analysis ultimately produces an RPN (Risk Priority Number) value. Based on FMEA calculations, it is known that the critical value is 46.92 where there are four RPN values that have more than that, the first is 173.25, the second is 105, the third is 70 and the last is 48.